Bureaucratic And Gender Reform In Development In Indonesia - Rahmadoni, Moh; Rahdin, Rahdin; Rahdian, Romario (Jurnal Pendidikan Ilmu Sosial, 2022)
This research wants to get a picture of bureaucratic reform in Semarang city government. This research method uses descriptive qualitative method with the aim of obtaining a complete picture of bureaucratic reform in realizing good governance in Semarang city government. Data analysis. The 1945 amendment has actually replaced the basic law of the Republic of Indonesia. Results and Discussion. The concept of bureaucrats that have been running for a long time in Indonesia, is a bureaucratic concept that functions as patriarchal and traditional, so the concept has changed into a transparent and transparent bureaucracy concept which is guided by the concept of good governance. Conclusion. One that supports bureaucratic reform is as a form of transformation of reforms in all fields, where one of them is the eradication of corruption, collusion and nepotism (KKN) in all fields.